Effect of Helicobacter pylori eradication on gastric cancer risk in patients with intestinal metaplasia or dysplasia: a meta-analysis of randomized controlled trials - Fu, Qiang; Yu, Huidong; Liu, Ming; Chen, Liang; Chen, Weiyang; Wang, Ziyi; Li, Wenya (Frontiers in Microbiology, 2025)
BackgroundObservational studies suggest that Helicobacter pylori (H. pylori) is associated with an increased risk of gastric cancer, yet the effect of H. pylori eradication on gastric cancer risk in patients with intestinal metaplasia (IM) or dysplasia remains controversial. The purpose of this study was to summarize the evidence from randomized controlled trials (RCTs) investigating H. pylori eradication on gastric cancer risk in patients with IM or dysplasia to determine the evidence base.MethodsPubMed, Embase, Cochrane Library, Web of science and China National Knowledge Internet database were searched for RCTs published through May 2024 in adults with IM or dysplasia comparing the risk of gastric cancer following H. pylori eradication versus no eradication therapy. Relative risk (RR) with its 95% confidence interval (CI) using random-effects model were employed for the effect estimate. Sensitivity, meta-regression, and subgroup analyses were also calculated.ResultsSixteen RCTs involving 15,027 patients with IM or dysplasia met the inclusion criteria. In a pooled analysis, H. pylori eradication resulted in a 45% reduction in RR for gastric cancer risk relative to no eradication (RR: 0.55; 95% CI: 0.46–0.67; p < 0.001). H. pylori eradication significantly reduced the risk of gastric cancer in patients with dysplasia (RR: 0.51; 95% CI: 0.32–0.82; p = 0.005), and IM (RR: 0.61; 95% CI: 0.40–0.93; p = 0.022). Further, if the study conducted in countries other than those in Asia, sample size <500, percentage of male <50.0%, follow-up duration <5.0 years, and low study quality, then there was no significant association between H. pylori eradication and a decreased risk of gastric cancer.ConclusionH. pylori eradication is protective against gastric cancer in patients with IM or dysplasia.Systematic review registrationINPLASY202530010, https://inplasy.com/.